Green Supply Chain Management and 3R on Wood Waste Utilization: A Systematic Literature Review - Sweet Nabila Imsaki Aulia; Ririn Indah Romadloni; Muhammad Fikri Maududi; Fenty Fauziah (www.amertainstitute.com, 2025)
This research aims to apply green supply chain management and 3R (reduce, reuse, recycle) to the utilization of wood waste and to determine to what extent wood waste is useful for human life. A total of 30 articles related to green supply chain management, 3R, and Wood Waste Utilization have been identified following the recommended systematic literature review methodology. The methodology in this research uses a systematic literature review approach. The systematic literature review research above shows that green supply chain management is combined with GIS for geospatial decision-making and the transportation of wood waste in the furniture industry to utilize wood waste. Wood waste is mainly produced by the woodworking or furniture industry as solid waste (wood chips, small pieces of wood, sawdust, and wood ash). By implementing green supply chain management and 3R in managing wood waste, it is hoped that wood waste will have added economic value and make more helpful use of waste. The results of wood waste management, such as mini carving crafts, particle board, and wood ash as a concrete mixture and shiny ceramics, biomass, and wood waste, are used to reduce iron oxide. Managing and utilizing wood waste will help increase the income of wood artisans and reduce production costs. Apart from that, managing wood waste as environmental preservation and maintaining forest sustainability. Like other systematic literature review studies, this research has limitations, such as translation procedures, data collection over time, and the need for systematic references. Future research can include additional variables interconnected with green supply chain management and 3R